TEACHER DOMINATION IN ENGLISH CLASSROOMS (RETAIN, 2015)
Abstract This study deals with teacher explanation in the frame of scientific approach classroom interaction. The objectives of this study are: (1) to find out the presence of teacher explanation in the classroom interaction, (2) to examine the amount of contribution of the teacher explanation to the classroom talk, and (3) to investigate the implication of the contribution to the students’ talk. The research design of this was case study research. An English teacher and the second year students of a senior high school in Bojonegoro were observed and recorded during the teaching learning processes. The classroom talks which have been recorded then transcribed and analyzed to answer the objectives of this study. The analysis data employed Analysis of Speech Units (AS-Units) and Conversation Analysis. There were three findings in this study, first, there was teacher explanation during teaching learning process, which was found in the observing, questioning, exploring, and analyzing stages. Second, the teacher explanation was dominating over classroom talk, which was proved by the highest contribution of informative mode over the other intentions found in the classroom interaction (24.96%). Last, the implications of this contribution to the students’ talk. First implication was that teacher explanation to the students’ talk in the frame of scientific approach. Second was that the students did not produce longer sentences since the teacher took up major portion of the interaction. It was proved by in one turn the teacher has produced three to four AS-Units meanwhile the students only produced one AS-Unit. Third, implication was that the students did not produce target language in the classroom since the teacher always asked the Indonesian words of the English expression of teacher’s utterance during the explanation. Keywords: Classroom Interaction, Teacher Explanation, student talk. Abstrak Penelitian ini berhubungan dengan penjelasan guru di kelas yang menggunakan Pendekatan Ilmiah. Tujuan penelitian ini diantaranya adalah: (1) melacak keberadaan penjelasan guru di setiap interaksi di kelas, (2) mengetahui jumlah kontribusi penjelasan guru terhadap jumlah ujaran di kelas, (3) mengetahui implikasi kontribusi tersebut pada ujaran siswa. Penelitian ini menggunakan studi kasus sebagai desain penelitian. Seorang guru bahasa inggris dan sejumlah siswa kelas XI salah satu SMA di Bojonegoro telah diobservasi dan direkam selama proses belajar mengajar sebagai sumber data dari penelitian ini. Setiap ujaran didalam kelas telah direkam untuk kemudian ditranskripsikan dan dianalasis guna menjawab tujuan penelitian ini. Data analisis yang dipergunakan adalah Analysis of Speech Units (AS-Units) dan Conversation Analysis. Ada 3 hasil yang telah didapatkan setelah pengambilan data, yang pertama, penjelasan guru ditemukan selama kegiatan belajar mengajar, diantaranya pada tahap mengamati, menanya, mengumpulkan, dan menganalisis. Yang kedua, penjelasan guru terbukti mendominasi ujaran di kelas, hal inii dibuktikan oleh tingginya kontribusi mode informative diantara semua mode (24,96%). Yang terakhir, implikasi dari kontribusi ini. Implikasi pertama adalah, pengaruh kontribusi ini pada ujaran siswa di setiap langkah di pendekatan ilmiah. Implikasi yang kedua adalah siswa tidak berbicara lebih panjang karena guru telah menjelaskan semuanya. Hal ini dibuktikan, pada satu kali giliran berbicara guru memproduksi tiga sampai empat AS-Units, sementara siswa hanya memproduksi satu AS-Units sebagai responnya. Implikasi ketiga adalah siswa tidak banyak berbicara dengan menggunakan bahasa inggris, hal ini dikarenakan guru selalu bertanya bentuk bahasa Indonesia dari setiap kata bahasa inggris yang diucapkannya selama guru menjelaskan. Kata Kunci: Interaksi kelas, Penjelasan Guru, ujaran siswa.